Molecular Ln(III)−H−E(II) Linkages (Ln=Y, Lu; E=Ge, Sn, Pb). Issue 45 (23rd June 2022) - Widemann, Max; Aicher, Frederik S. W.; Bonath, Martin; Eichele, Klaus; Maichle‐Mössmer, Cäcilia; Schubert, Hartmut; Sirsch, Peter; Anwander, Reiner; Wesemann, Lars
Abstract: Following the alkane‐elimination route, the reaction between tetravalent aryl tintrihydride Ar*SnH3 and trivalent rare‐earth‐metallocene alkyls [Cp*2 Ln(CHSiMe3 2 )] gave complexes [Cp*2 Ln(μ‐H)2 SnAr*] implementing a low‐valent tin hydride (Ln=Y, Lu; Ar*=2, 6‐Trip2 C6 H3, Trip=2, 4, 6‐triisopropylphenyl). The homologous complexes of germanium and lead, [Cp*2 Ln(μ‐H)2 EAr*] (E = Ge, Pb), were accessed via addition of low‐valent [(Ar*EH)2 ] to the rare‐earth‐metal hydrides [(Cp*2 LnH)2 ]. The lead compounds [Cp*2 Ln(μ‐H)2 PbAr*] exhibit H/D exchange in reactions with deuterated solvents or dihydrogen. Abstract : Reductive alkane elimination reacting the aryltin trihydride Ar*SnH3 with donor free alkyl complexes [Cp*2 Ln(CHSiMe3 2 )] (Ln=Y, Lu) in the presence of diethyl methylamine gives access to Ln(III)−H−Sn(II) linkages. The respective germanium and lead entities can be generated via exchange of hydrido‐bridged dimers [(Ar*EH)2 ] (E=Ge, Pb) and [(Cp*2 Ln(μ‐H)2 ] (Ln=Y, Lu). Lead derivatives [Cp*2 Ln(μ‐H)2 PbAr*] engage in H/D‐exchange in benzene‐d6 at ambient temperature.